Limits of Monetary Policy Autonomy and Exchange Rate Flexibility by East Asian Central Banks - Axel Löffler; Gunther Schnabl; Franziska Schobert (Graduiertenkolleg 'Konstitutionelle Grundlagen globalisierter Finanzmärkte - Stabilität und Wandel', 2013)
Given low interest rates in the large industrial countries and buoyant capital inflows into the emerging markets East Asian central banks have accumulated large stocks of foreign reserves. As the resulting easing of monetary conditions has become a threat to domestic price and financial stability, the East Asian central banks have embarked on substantial sterilization operations to absorb what we call 'surplus liquidity' from the domestic banking systems. This has brought the East Asian central banks into debtor positions versus the domestic banking systems. We show based on a central bank loss function that given buoyant capital inflows and exchange rate stabilization the absorption of surplus liquidity leads either to financial repression, or rising inflation or both. Assuming that a debtor central bank moved towards a freely floating exchange rate to gain monetary policy independence, we show that monetary policy independence is undermined by sterilization costs and revaluation losses on foreign reserves.
urn:nbn:de:gbv:27-20131126-154313-8
Keywords: E52; E58; F31; 330; Debtor Central Banks; Monetary Policy Autonomy; Sterilization; Exchange Rate Regime; East Asia